Gut microbiota condition the therapeutic efficacy of trastuzumab in HER2-positive breast cancer - Di Modica, Martina; Gargari, Giorgio; Regondi, Viola; Bonizzi, Arianna; Arioli, Stefania; Belmonte, Beatrice; De Cecco, Loris; Fasano, Elena; Bianchi, Francesca; Bertolotti, Alessia; Tripodo, Claudio; Villani, Laura; et al. (Cancer Research, 2021)
Abstract Emerging evidence indicates that gut microbiota affect the response to anticancer therapies by modulating the host immune system. In this study, we investigated the impact of gut microbiota on immune-mediated trastuzumab antitumor efficacy in preclinical models of HER2-positive breast cancer and in 24 patients with primary HER2-positive breast cancer undergoing trastuzumab-containing neoadjuvant treatment. In mice, the antitumor activity of trastuzumab was impaired by antibiotic administration or fecal microbiota transplantation from antibiotic-treated donors. Modulation of the intestinal microbiota was reflected in tumors by impaired recruitment of CD4+ T cells and granzyme B–positive cells after trastuzumab treatment. Antibiotics caused reductions in dendritic cell (DC) activation and the release of IL12p70 upon trastuzumab treatment, a mechanism that was necessary for trastuzumab effectiveness in our model. In patients, lower α-diversity and lower abundance of Lachnospiraceae, Turicibacteraceae, Bifidobacteriaceae, and Prevotellaceae characterized nonresponsive patients (NR) compared with those who achieved pathologic complete response (R), similar to antibiotic-treated mice. The transfer of fecal microbiota from R and NR into mice bearing HER2-positive breast cancer recapitulated the response to trastuzumab observed in patients. Fecal microbiota β-diversity segregated patients according to response and positively correlated with immune signature related to interferon (IFN) and NO2-IL12 as well as activated CD4+ T cells and activated DCs in tumors. Overall, our data reveal the direct involvement of the gut microbiota in trastuzumab efficacy, suggesting that manipulation of the gut microbiota is an optimal future strategy to achieve a therapeutic effect or to exploit its potential as a biomarker for treatment response. Significance: Evidence of gut microbiota involvement in trastuzumab efficacy represents the foundation for new therapeutic strategies aimed at manipulating commensal bacteria to improve response in trastuzumab-resistant patients. See related commentary by Sharma, p. 1937